Pemberdayaan Masyarakat Kelurahan Sukajadi Timur Melalui Literasi Digital dan Kegiatan Sosial Keagamaan - Muhtarom .; Reva Azzahra Triana; Intan Mervinasari; Velisa Destiria; Dhea Ananda; Ririn Ulandari (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Community empowerment in the digital age requires an approach that is not only oriented towards economic capacity building, but also the strengthening of social and religious values within the community. This article aims to analyse the implementation of community empowerment programmes in Sukajadi Timur Sub-District through the integration of digital literacy and religious social activities as a community-based development model. The research uses a descriptive qualitative approach with a participatory design involving MSME actors, youth, community leaders, and local residents as research subjects. Data were collected through participatory observation, semi-structured interviews, activity documentation, and reflective discussions, then analysed using thematic analysis techniques. The results of the study indicate that digital literacy training improves the online marketing capabilities of MSMEs, broadens teenagers' understanding of digital ethics, and increases the community's confidence in utilising technology. On the other hand, religious social activities strengthen social cohesion, community participation, and value stability in the face of digital change. The integration of these two aspects produces a multidimensional empowerment model, covering simultaneous economic, social, and moral capacity building, and has the potential to become a sustainable empowerment strategy at the village level.